The use of Nano-Encapsulation of Morinda citrifolia Fruit Extract in Drinking Water as Phytobiotic Based Feed Additive in laying Hens - Choiri, Zainal (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was aimed to analyze the effect of nano-encapsulation of noni fruit extract (NFE) utilization in drinking water as phytobiotic based feed additive in layer phase of laying hens. The experiment was conducted in a completely randomized design consisting of 6 treatments and 5 replicates, with 12 chickens in each replicate pen. The treatments were: P0 = drinking water without feed additive (negative control); P1 = drinking water + Tetracycline 50 mg/hen (positive control); P2 = drinking water + 0.5% extract of noni fruit; P3 = drinking water + 0.5% nano-encapsulation of NFE; P4 = drinking water + 1% nano-encapsulation of NFE; P5 = drinking water + 1.5% nano-encapsulation of NFE. The observed parameter was productive performance of laying hens, which include: daily feed intake, egg production, feed conversion ratio, and egg mass. Data were statistically analyzed using oneway ANOVA. Results showed that supplementation of nano-encapsulation of noni fruit extract in drinking water with the level of 1.5% did not affect productive performance of laying hens, such as: feed intake, hen day production, egg mass, and feed conversion ratio. Supplementation of antibiotic in low level in current study did not also give any significant effect. It can be concluded that supplementation of 1.5% nano-encapsulation of noni fruit extract via drinking water administration did not influential for maximizing productive performance of laying hens. The use of NFE gave the same result as antibiotic use.